The great convergence Asia, the West, and the logic of one world - Mahbubani, Kishore (New York PublicAffairs, 2013)
"Before the current international economic crisis, Asian policymakers deferred to their Western counterparts. The enormous blunders since committed by the US and Europe mean deference has been replaced by disquiet. Asia's concern is that the world will soon come to grief if both the US and Europe fail to make fundamental readjustments. An America and EU that takes serious economic measures will cause the rest of the world pain, as Western consumption and imports diminish. But there is no painless solution: only when the West gets its house in order can Asia hope for a more sustainable future"--
A new global civilization -- A theory of one world -- Global irrationality -- Seven global contradictions -- Will geopolitics derail convergence? -- A barrier to convergence -- Converging on global convergence -- Conclusion : because everything that rises must converge
Includes bibliographical references (pages 275-297) and index
1
Keywords: East and West; Global Financial Crisis, 2008-2009; Globalization; International economic relations; International relations; Asia -- Foreign economic relations; Asia -- Foreign relations